Real‐time RT‐PCR profiling of over 1400 Arabidopsis transcription factors: unprecedented sensitivity reveals novel root‐ and shoot‐specific genes - Czechowski, Tomasz; Bari, Rajendra P.; Stitt, Mark; Scheible, Wolf‐Rüdiger; Udvardi, Michael K. (The Plant journal : for cell and molecular biology, 2004)
Summary To overcome the detection limits inherent to DNA array‐based methods of transcriptome analysis, we developed a real‐time reverse transcription (RT)‐PCR‐based resource for quantitative measurement of transcripts for 1465 Arabidopsis transcription factors (TFs). Using closely spaced gene‐specific primer pairs and SYBR® Green to monitor amplification of double‐stranded DNA (dsDNA), transcript levels of 83% of all target genes could be measured in roots or shoots of young Arabidopsis wild‐type plants. Only 4% of reactions produced non‐specific PCR products. The amplification efficiency of each PCR was determined from the log slope of SYBR® Green fluorescence versus cycle number in the exponential phase, and was used to correct the readout for each primer pair and run. Measurements of transcript abundance were quantitative over six orders of magnitude, with a detection limit equivalent to one transcript molecule in 1000 cells. Transcript levels for different TF genes ranged between 0.001 and 100 copies per cell. Only 13% of TF transcripts were undetectable in these organs. For comparison, 22K Arabidopsis Affymetrix chips detected less than 55% of TF transcripts in the same samples, the range of transcript levels was compressed by a factor more than 100, and the data were less accurate especially in the lower part of the response range. Real‐time RT‐PCR revealed 35 root‐specific and 52 shoot‐specific TF genes, most of which have not been identified as organ‐specific previously. Finally, many of the TF transcripts detected by RT‐PCR are not represented in Arabidopsis EST (expressed sequence tag) or Massively Parallel Signature Sequencing (MPSS) databases. These genes can now be annotated as expressed.